PENGARUH BIMBINGAN KONSELING ISLAM TERHADAP PENINGKATAN MORAL ANAK JALANAN DI SANGGAR ALANG-ALANG SURABAYA (Jurusan Bimbingan dan Konseling Islam, 2013)
There are two discussions that were examined in this thesis are: ( 1 ) how the implementation of Islamic counseling to the moral improvement of street children, ( 2 ) there Counseling influence of Islam on the moral improvement of street children in Alang - Alang Studio Surabaya. The purpose of this research is : to know the implementation of Guidance and Counselling Islam against the moral improvement of street children in Alang - Alang Studio Surabaya and to determine whether there is influence of Islamic Guidance and Counselling for moral improvement of street children in studio reeds Surabaya. In this study the method of quantitative descriptive analysis to determine moment prodak The lack of guidance counseling influence of Islam on the moral enhancement. Based on the research results of the implementation of Islamic Guidance and Counselling against the moral improvement of street children in Surabaya Studio Reed performed with two forms of individuals and groups, while the results of the 0275 then there is no influence of Islamic counseling to the moral improvement of street children.Keywords : Islamic Counseling, Moral Development, Street Children